A longitudinal study of higher-order thinking skills: working memory and fluid reasoning in childhood enhance complex problem solving in adolescence - Greiff, Samuel; Wüstenberg, Sascha; Goetz, Thomas; Vainikainen, Mari-Pauliina; Hautamäki, Jarkko; Bornstein, Marc H. (Frontiers in Psychology, 2015)
Scientists have studied the development of the human mind for decades and have accumulated an impressive number of empirical studies that have provided ample support for the notion that early cognitive performance during infancy and childhood is an important predictor of later cognitive performance during adulthood. As children move from childhood into adolescence, their mental development increasingly involves higher-order cognitive skills that are crucial for successful planning, decision-making, and problem solving. Importantly, few studies have employed higher-order thinking skills such as Complex Problem Solving (CPS) as developmental outcomes in adolescents. To fill this gap, we tested a longitudinal developmental model in a sample of 2,021 Finnish sixth grade students (M = 12.41 years, SD = 0.52; 1,041 female, 978 male, 2 missing sex). We assessed working memory and fluid reasoning at age 12 as predictors of two CPS dimensions: knowledge acquisition and knowledge application. We further assessed students’ CPS performance 3 years later as a developmental outcome (N= 1696; M = 15.22 years, SD = 0.43; 867 female, 829 male). Missing data partly occurred due to dropout and technical problems during the first days of testing and varied across indicators and time with a mean of 27.2%. Results revealed that fluid reasoning was a strong predictor of both CPS dimensions, whereas working memory exhibited only a small influence on one of the two CPS dimensions. These results provide strong support for the view that CPS involves fluid reasoning and, to a lesser extent, working memory in childhood, and from there evolves into an increasingly complex structure of higher-order cognitive skills in adolescence.